Mathematical Modeling of the Linear Alkylbenzene Sulfonation Process in A Multitube Film Reactor; Petroleum and Coal; Vol. 63, iss. 1 - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna; Dolganov I. M. Igor Mikhailovich; Solopova A. A. Anastasia Alexandrovna (2021, 2021)
Title screen